50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Facility Background Pressure on the Performance and Operation of the High Voltage Hall Accelerator

Abstract: The National Aeronautics and Space Administration (NASA) Science Mission Directorate In-Space Propulsion Technology office is sponsoring NASA Glenn ResearchCenter to develop a 4 kW-class Hall thruster propulsion system for implementation in NASA science missions. A study was conducted to assess the impact of varying the facility background pressure on the High Voltage Hall Accelerator (HiVHAc) thruster performance and voltage-current characteristics. This present study evaluated the HiVHAc thruster performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…However, as the Hall thruster power and efficiency increase, a significant departure from predicted on-orbit operation based on ground test and simulation data has brought into question the validity of established pressure limits for thruster qualification. Typical pressures seen in research and development vacuum facilities during thruster operation are ∼1-5 × 10 −5 torr, with world-class test and evaluation facilities such as the NASA John H. Glenn Research Center's Vacuum Facility 5 approaching low 10 −6 or middle 10 −7 torr, depending on the propellant flow rate of the thruster [8]. Even these lower pressures are orders of magnitude higher than the less than 1 × 10 −10 torr seen at geostationary orbit.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the Hall thruster power and efficiency increase, a significant departure from predicted on-orbit operation based on ground test and simulation data has brought into question the validity of established pressure limits for thruster qualification. Typical pressures seen in research and development vacuum facilities during thruster operation are ∼1-5 × 10 −5 torr, with world-class test and evaluation facilities such as the NASA John H. Glenn Research Center's Vacuum Facility 5 approaching low 10 −6 or middle 10 −7 torr, depending on the propellant flow rate of the thruster [8]. Even these lower pressures are orders of magnitude higher than the less than 1 × 10 −10 torr seen at geostationary orbit.…”
Section: Introductionmentioning
confidence: 99%
“…15 During the test, thrust, current-voltage (I-V) characteristics, and a number of plasma diagnostics were implemented to study the effect of varying the facility background pressure on thruster operation. 16 These diagnostics include thrust stand, Faraday probe, ExB probe, and retarding potential analyzer. 17 The test results indicated a rise in thrust and discharge current with background pressure.…”
Section: High Voltage Hall Acceleratormentioning
confidence: 99%
“…Previous investigations in other thrusters have observed that the acceleration zone and plasma recede further into the channel towards the anode with elevated facility pressure. 19,[28][29][30][31][32] In particular, this shift was observed to cause increased electron temperatures along the channel walls of the HiVHAc Hall thruster. 19 It is possible that a similar shift in the plasma is occurring towards the anode, resulting in slightly elevated temperatures at higher pressure.…”
Section: A Axial Profiles Under Nominal Conditionsmentioning
confidence: 99%